Effect of Morning Exercise With or Without Breaks in Prolonged Sitting on Blood Pressure in Older Overweight/Obese Adults: Evidence for Sex Differences. Issue 4 (April 2019) - Wheeler, Michael J.; Dunstan, David W.; Ellis, Kathryn A.; Cerin, Ester; Phillips, Sarah; Lambert, Gavin; Naylor, Louise H.; Dempsey, Paddy C.; Kingwell, Bronwyn A.; Green, Daniel J.
Abstract : Both exercise and breaks in prolonged sitting can reduce blood pressure (BP) in older overweight/obese adults. We investigated whether there is an additive hypotensive effect when exercise is combined with subsequent breaks in sitting. Sex differences and changes in plasma catecholamines as a potential candidate mechanism underlying BP responses were also examined. Sedentary older adults (n=67; 67±7 years; 31.2±4.1 kg/m 2 ) completed 3 conditions in random order—sitting (SIT): uninterrupted sitting (8 hours, control); exercise+sitting (EX+SIT): sitting (1 hour), moderate-intensity walking (30 minutes), uninterrupted sitting (6.5 hours); exercise+breaks (EX+BR): sitting (1 hour), moderate-intensity walking (30 minutes), sitting interrupted every 30 minutes with 3 minutes of light-intensity walking (6.5 hours). Serial BP and plasma epinephrine/norepinephrine measurements occurred during 8 hours. The 8-hour average systolic and diastolic BP (mm Hg 95% CI) was lower in EX+SIT −3.4 (−4.5 to −2.3), −0.8 (−1.6 to −0.04), and EX+BR −5.1 (−6.2 to −4.0), −1.1 (−1.8 to −0.3), respectively, relative to SIT (all P <0.05). There was an additional reduction in average systolic BP of −1.7 (−2.8 to −0.6) in EX+BR relative to EX+SIT ( P =0.003). This additional reduction in systolic BP was driven by women −3.2 (−4.7 to −1.7; P <0.001 EX+BR versus EX+SIT). Average epinephrine decreased in EX+SIT and EX+BR in women (−13% to −12%) but increased in men (+12% to +23%), respectively, relative to SIT ( P <0.05). No differences in average norepinephrine were observed. Morning exercise reduces BP during a period of 8 hours in older overweight/obese adults compared with prolonged sitting. Combining exercise with regular breaks in sitting may be of more benefit for lowering BP in women than in men. Clinical Trial Registration—: URL:https://www.anzctr.org.au . Unique identifier: ACTRN12614000737639. Abstract : Supplemental Digital Content is available in the text.